Perbaikan Teknis Sistem Pencatatan Persediaan Barang Berbasis Komputer Bagi Pedagang Buku Pasar Palasari Kota Bandung Menghadapi Era Pasar Kompetitif - Zen Munawar; Mira Ismirani Fudsyi; Dadad Zainal Musadad (Universitas Tribhuwana Tunggadewi Malang, 2020)
The Palasari Book Market in the city of Bandung was moved from the Cikapundung Book Market in 1975 located above the Palasari traditional market. When consumers look for books with specific titles such as those of writers with visitors looking for a book entitled